Impact of low back pain and care-seeking behavior in an Indigenous community in Suriname: a qualitative approach - Niels Struyf; Yano Truyers; Tom Vanwing; Wolfgang Jacquet; Hans Paraanen; Nancy Ho-; Wim Dankaerts (James Cook University, 2024)
Introduction: Low back pain is a significant global public health issue affecting over half a billion people and contributing to disability worldwide. The impact of disability related to low back pain is growing, particularly in low- and middle-income countries. In contrast with previous research, current evidence shows Indigenous Peoples also experience low back pain's disabling effects. A clinical ethnographic can contribute by attempting to understand the data through the perspective of Indigenous Peoples. Methods: A clinical ethnographic study was conducted in Galibi, a Kalinya rural Indigenous village in Suriname, with support of the local traditional authority. The main objective was to explore the impact of low back pain and care-seeking behavior from the perspective of Indigenous Peoples with low back pain. Results: The findings were that low back pain had a significant physical and emotional impact. Despite aggravating their low back pain, participants continued many of their activities of daily life since these were essential for their (economic) survival. Furthermore, participants expressed anxiousness, financial worries, and concerns about the cause and future of their low back pain. To address their low back pain, the Kalinya Indigenous Peoples used both western and traditional care. Visits to western healthcare practitioners were limited due to logistical challenges and travel costs, and the experience was often negative. Conclusion: The study highlights the experiences of Kalinya Indigenous Peoples dealing with low back pain. Low back pain is a burden within Indigenous Peoples of Galibi but accepted as an integral part of their life. When in pain, Indigenous Peoples face many barriers to access western health care and visits to healthcare practitioners were often unhelpful. This contributed to a long-lasting negative impact on the Indigenous people with low back pain. Further research is needed to develop strategies that improve health outcomes related to low back pain while reducing its associated disability in Indigenous Peoples.